EFFECT OF CUTTING AND NITROGEN MANAGEMENT ON PLANT MATURITY AND SEED SET IN OAT CV. JHO-851(AVENA SATIVA L.) - M. S, PUNEETH RAJ; B. S. , VYAKARANAHAL (The Bioscan, 2016)
The field experiment was carried out at UAS, Dharwad, in the department of Seed Science and Technology during Rabi season of 2012 and 2013for 2 year with the following treatments N1 : 80 kg/ha, N2: 100kg/ha, N3: 120kg/ha, N4: 140kg/ha. Cutting management: C1 : No cut, C2 : one cut, C3 : two cut and for all treatments 60:40 P2 O5 , K2 O per ha, nitrogen is varied.Resultsrevealed that application of 80:60:40, N, P2 O5 , K2 O kg/ha showed significant plant performance such as early plant maturity, early days to 50 % flowering for the application of 60:40, P2 O5 : K2 O Per ha + 80kgN/ha 131.02 days and with no cut93.06 days and forthe seed set %significantly higher seed set % forthe application of 60:40, P2 O5: K2O Per ha + 140kgN/ha81.99 (%)andwith no cut 83.89 (%) and in seeds per panicle showed significantly higher in no cut recorded 68.52 and for the application of 60:40, P2 O5 : K2 O Per ha + 140kgN/ha showed significantly higher 66.73 seeds per panicle.The data can be concluded with no cut and 140kgN/ha showed significantly higher seed quality parameters.